1998
DOI: 10.1074/jbc.273.19.11417
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of an Active Site Residue of Tryptophan Synthase (β-Serine 377) Alters Cofactor Chemistry

Abstract: To better understand how an enzyme controls cofactor chemistry, we have changed a tryptophan synthase residue that interacts with the pyridine nitrogen of the pyridoxal phosphate cofactor from a neutral Ser (␤-Ser 377 ) to a negatively charged Asp or Glu. The spectroscopic properties of the mutant enzymes are altered and become similar to those of tryptophanase and aspartate aminotransferase, enzymes in which an Asp residue interacts with the pyridine nitrogen of pyridoxal phosphate. The absorption spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
30
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 41 publications
11
30
0
Order By: Relevance
“…Jhee et al (26) mutated the pyridine nitrogen-contacting serine in tryptophan synthetase (S377) to aspartate and found that a quinonoid intermediate accumulates. Grishin et al (8) proposed that ornithine decarboxylase has an R/ barrel fold like alanine racemase, yet this enzyme appears to have an aspartate residue interacting with the PLP pyridine nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Jhee et al (26) mutated the pyridine nitrogen-contacting serine in tryptophan synthetase (S377) to aspartate and found that a quinonoid intermediate accumulates. Grishin et al (8) proposed that ornithine decarboxylase has an R/ barrel fold like alanine racemase, yet this enzyme appears to have an aspartate residue interacting with the PLP pyridine nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…a positive charge at N1 is not a prerequisite for PLP to become catalytically effective. The effect of the group interacting with N1 on the electron distribution within the cofactor has been experimentally probed by site-directed mutagenesis experiments with aspartate aminotransferase of the a family (Yano et al, 1992;Onuffer and Kirsch, 1994) and the P-subunit of tryptophan synthase of the p family (Jhee et al, 1998). (3) K ions have been found to be essential for catalytic activity of particular B, enzymes such as 2,2-dialkylglycine decarboxylase (Toney et al, 1993(Toney et al, , 1995, tryptophan synthase P (Rhee et al, 1996), tyrosine phenol-lyase Sundararaju et al, 1997), and tryptophan phenol-lyase (tryptophanase; Isupov et al, 1998).…”
Section: F Divergence In Catalytic Mechanismsmentioning
confidence: 99%
“…The mutation of TRPS␤ introducing asparate or glutamate residues at the position of this serine residue stabilized the protonated form of pyridine nitrogen of PLP, reducing the pK a of the internal aldimine nitrogen and promoting the formation of quinonoid intermediate (40). Consequently, the mutant enzyme of TRPS␤ with asparate residue interacting with the pyridine nitrogen showed a pH-dependent absorption spectrum and mechanism-based inactivation by Lserine (40).…”
mentioning
confidence: 97%
“…The mutation of TRPS␤ introducing asparate or glutamate residues at the position of this serine residue stabilized the protonated form of pyridine nitrogen of PLP, reducing the pK a of the internal aldimine nitrogen and promoting the formation of quinonoid intermediate (40). Consequently, the mutant enzyme of TRPS␤ with asparate residue interacting with the pyridine nitrogen showed a pH-dependent absorption spectrum and mechanism-based inactivation by Lserine (40). The absorption band shifted from 336 nm at around pH 9 to 416 nm at around pH 6.5, and incubation of the mutant enzyme with L-serine formed a covalent adduct of internal aldimine and aminoacrylate, which was confirmed by spectral data and a compound released from the adduct by alkaline.…”
mentioning
confidence: 99%